COMPARATIVE EVALUATION OF THE EFFECTIVENESS OF FIVE METHODS FOR EARLY DIAGNOSIS OF OCCLUSAL CARIES LESIONS - in vitro study. - Mirela Marinova-Takorova; Radostina Anastasova; Vladimir E. Panov (Peytchinski Publishing, 2014)
Purpose: The aim of the presented in vitro study was to evaluate the effectiveness of the device DIAGNOcam and the laser fluorescence device DIAGNOdent for early diagnosis of occlusal caries and to compare it with three traditional methods - visual and tactile, dye and radiographic examination. Material and methods: The sample consisted of 60 extracted human teeth. Three clinicians diagnosed independently the presence or absence of early occlusal surface caries with the visible tactile method,DIAGNOcam andDIAGNOdent. Then X-rays were taken and the dentists viewed them separately, without magnification.Fuchsine was applied for 30 sec. and then washed under running water for 20 min. Places where dye was present were registered. Statistical analysis was performed with SPSS package of Windows. Results: The results showed high level of correspondence between the authors for all the diagnostic methods. Concerning different methods applied for caries diagnosis there was a correlation between the methods, but it was diverging for the different methods. No correlation between radiographic exam and data obtained with DIAGNOdent and dye staining was observed. Conclusions: Based on the obtained results we may conclude that the least sensitive method for fissure caries diagnosis was the dye staining, followed by the radiographic exam. The results, obtained by DIAGNOdent and DIAGNOcam were very close, but DIAGNOcams' data was better correlating with the clinical results.DIAGNOcam procedure can be judged as equivalent in the detection of occlusal dentine lesions when compared to clinical results.